Transformational innovation in home energy: How developers imagine and engage with future residents of low carbon homes in the United Kingdom. (September 2022) - Shirani, Fiona; O'Sullivan, Kate; Hale, Rachel; Pidgeon, Nick; Henwood, Karen
Abstract: Decarbonisation and climate change targets require multiscale sociotechnical energy transitions that include significant changes to housing stock. In the UK, the development of Active Buildings, which directly seek to be efficient energy producers, have zero carbon emissions and provide grid flexibility, has the potential to make a significant contribution to meeting these targets. Active Homes as a particular type of Active Building represent a potentially transformational innovation by altering how energy is produced, distributed and consumed, in addition to how homes are designed, constructed and then lived in. In this paper we draw on insights from qualitative interviews with stakeholders involved in the development of different Active Homes to consider motivations for development, and their views on how residents will reside in and interact with the homes. We highlight a potential conflict between a desire to prioritise the needs of residents with a belief amongst some that to do so, user engagement with technology should be minimised. This has implications for design decisions, which in turn influence how residents experience and live within the homes. In illuminating these narratives, we indicate the necessity of ongoing engagement with residents to understand how Active Homes – with particular emphasis on the operation and control of technologies – are experienced, in order to inform the successful rollout of current and future developments.